2007
DOI: 10.1016/j.sleep.2007.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and neurobiological aspects of narcolepsy

Abstract: Narcolepsy is characterized by excessive daytime sleepiness (EDS), cataplexy and/or other dissociated manifestations of rapid eye movement (REM) sleep (hypnagogic hallucinations and sleep paralysis). Narcolepsy is currently treated with amphetamine-like central nervous system (CNS) stimulants (for EDS) and antidepressants (for cataplexy). Some other classes of compounds such as modafinil (a non-amphetamine wake-promoting compound for EDS) and gamma-hydroxybutyrate (GHB, a short-acting sedative for EDS/fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
93
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(98 citation statements)
references
References 176 publications
(242 reference statements)
0
93
0
5
Order By: Relevance
“…The hcrt system has an important wake-promoting function and is involved in the control of motor activity. A defect in the hcrt-2 receptor, as well as destruction of hcrt-containing neurons in the hypothalamus, have been determined as causative factors in the canine and human forms of the sleep disorder, narcolepsy [26]. Interestingly, survey investigations have reported that BMI may be elevated in narcoleptic patients [27], and animal studies indicate that feeding and energy expenditure problems in hcrt deficient mice are directly related to the disruption in sleep-wake patterns [28].…”
Section: Effects Of Altered Metabolism On Sleep-wake Patternsmentioning
confidence: 99%
“…The hcrt system has an important wake-promoting function and is involved in the control of motor activity. A defect in the hcrt-2 receptor, as well as destruction of hcrt-containing neurons in the hypothalamus, have been determined as causative factors in the canine and human forms of the sleep disorder, narcolepsy [26]. Interestingly, survey investigations have reported that BMI may be elevated in narcoleptic patients [27], and animal studies indicate that feeding and energy expenditure problems in hcrt deficient mice are directly related to the disruption in sleep-wake patterns [28].…”
Section: Effects Of Altered Metabolism On Sleep-wake Patternsmentioning
confidence: 99%
“…2a) at all three sessions. This question could be addressed in terms of dysfunction of the hypocretin system in NC patients (for review, see Nishino, 2007) and tested by establishing (i) whether the low level of initial learning depends mainly on deficits in executive functions caused by the allocation of cognitive resources to monitor and maintain vigilance. Some support for this hypothesis (recently suggested by Naumann et al, 2006) could be found in the slight, but significantly lower accuracy in letter recognition of NC patients relative to controls (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Dear Editor, Narcolepsy is a sleep disorder that causes functional impairment and it is underdiagnosed since it is rare (1). Main symptoms of narcolepsy include daytime excessive sleepiness and sleep attacks, cataplexia due to sudden loss of muscle tone in response to planned or unexpected situations, sleep paralysis, hypnogogic and hypnopompic hallucinations (2).…”
mentioning
confidence: 99%
“…Main symptoms of narcolepsy include daytime excessive sleepiness and sleep attacks, cataplexia due to sudden loss of muscle tone in response to planned or unexpected situations, sleep paralysis, hypnogogic and hypnopompic hallucinations (2). The term "narcolepsy" was used for the first time in 1880 by a French physician, Gélinea, to describe excessive sleepiness during daytime, sleep attacks and muscle weakness triggered by emotions in a patient (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation